ANALISIS POTENSI REVITALISASI PELAYANAN ANGKUTAN UMUM PERKOTAAN DI KOTA PONTIANAK MENGGUNAKAN METODE DESCRIPTIVE ANALYSIS DAN K-INDEPENDENT-SAMPLES TEST - Said Basalim; Akhmadali Akhmadali; Meta Indah Fitriani (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2022)
The two city transportation terminals, currently operating regularly, are located in Pontianak City, which is: Siantan Terminal and Cempaka Terminal. This study examines the characteristics of users, who recently utilized public transportation. The methods used in this study are interviews and statistical data, processed with descriptive analysis and K-independent-Samples Test. From the descriptive analysis, it was revealed that the most users based on age were in the range of 31-40 to 61-70 years, amounting to 60-80% per terminal. Especially in Siantan Terminal, there are users in the age range of 10-20, consisting of school students in a high percentage (23.2%). Based on gender, the users of both terminals are dominated by women, which are 56% in Siantan Terminal and 62.61% in Cempaka Terminal, respectively. For user characteristics based on the type of work, housewives are dominant in both terminals, which are 37.6% and 46.09%, respectively. Based on income level, public transport users in both terminals are dominated by people with low incomes (under IDR 1 million per month). As for travel purposes, in line with the previous study results, shopping in the two terminals becomes the most travel purpose, which is 44% and 53.04%, respectively. The results of this study indicate that women, adults and the elderly, students, and low-income communities become the segments of the public using public transportation, which can be maintained as users of public transportation. The analysis results using the K-Independent-Samples Test indicate that variations in the variables of gender and income level have a significant impact on the frequency of using public transportation. From the results of the analysis as described above, the revitalization and duplication of public transport services and passenger terminals are eligible to be conducted for other areas in Pontianak City.